STUDY PREVALENCE AND EFFECT OF INTERNAL PARASITES AND HISTOPATHOLOGICAL CHANGES ON COMMON FROGS AT BAGHDAD CITY - & et al., Al-Khamesi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
A total of seventy adult common frogs [sixty infected (85.71%) and ten healthy (14.29%) specimens], were collected from different areas of Baghdad city in more than one locations such as (agriculture lands, river banks, home gardens, ponds, streams and shoel water) from the beginning of September 2016 to the end of March 2017 and examined for parasites, in the aim to study and isolate any parasitic infection from intestine, blood and effect of these parasites on blood, intestine and liver in common frogs. Thus resulting in Opalina sp. 17(28.33%), Nematodes (Strongloides stercoralis) 14(23.33%), Balantidium sp. 14(23.33%), (Opalina Sp. & Nematodes) 7(11.66%) and Hepatozoon Spp. 8(13.33%). All these parasites which mentioned above not appeared any pathological effect on intestine of infected frogs according to histopathological sections. On the other hand, the current study showed the effect of blood parasites (Hepatozoon spp.) in the blood and liver of infected frogs like disappeared of nucleus in red blood cells , in addition to inflammation and infiltration which appeared in histopathological sections of hepatic cells compared with healthy specimens. Finally, we conclude from this study , the parasites which isolates from intestine of infected frogs has a commensalism relationship with its hosts due to not appeared any pathological effect on it, while the blood parasites showed pathological effect on blood and liver of infected frogs.